Analysis of Social Media Engagement for Archipelago Tourists in West Java Province - Amanda Putri, Maitsa; Hendriyani, Chandra; Sitti Rochmah, Tengku (Fakultas Pendidikan Ekonomi dan Bisnis, 2023)
This study aims to analyze social media engagement for domestic tourists in West Java province. In today's digital era, social media has become an important platform for sharing experiences and information about tourist destinations. This research focuses on Instagram and TikTok engagement of the West Java Tourism Office. The research method uses a descriptive qualitative method with data collection techniques using secondary data and the results of the analysis using the Analysis. or application. The data collected includes the results of performance analysis on a social media platform and past data. Based on research, it is known that TikTok has a higher engagement of 1.23% than Instagram, only 0.99%, which can also be seen from the number of likes, comments, and shares. Because the findings of the engagement rate are still below 5%, the authors suggest increasing creativity in creating content for published materials